2015
DOI: 10.1111/inm.12111
|View full text |Cite
|
Sign up to set email alerts
|

Consumer participation in nurse education: A national survey of Australian universities

Abstract: Consumers of mental health services have an important role to play in the higher education of nursing students, by facilitating understanding of the experience of mental illness and instilling a culture of consumer participation. Yet the level of consumer participation in mental health nursing programmes in Australia is not known. The aim of the present study was to scope the level and nature of involvement of consumers in mental health nursing higher education in Australia. A cross-sectional study was underta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
73
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 20 publications
1
73
0
1
Order By: Relevance
“…Despite the acknowledged benefits, involving EBEs in educating nurses and other healthcare professionals remains in its infancy and generally occurs on a limited and ad hoc basis (Happell et al . ; McCann et al . ; Meehan & Glover ) and is frequently confined to the use of story (Happell & Bennetts ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the acknowledged benefits, involving EBEs in educating nurses and other healthcare professionals remains in its infancy and generally occurs on a limited and ad hoc basis (Happell et al . ; McCann et al . ; Meehan & Glover ) and is frequently confined to the use of story (Happell & Bennetts ).…”
Section: Discussionmentioning
confidence: 99%
“…Their study found that the majority of consumers in tertiary nurse education contributed between 1 and 4 hours’ participation to a curriculum (Happell et al . ). The study presented in the present paper focussed on a novel approach to the inclusion of consumers for nurse student education, where students and consumers lived together for 4 nights and 5 days.…”
Section: Discussionmentioning
confidence: 97%
“…This is a much longer period of time than that identified by Happell et al . (). In the present study, consumer involvement occurred in a clinical placement capacity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations